La lengua guaraní dependiente en tiempos de Independencia en Paraguay - Bartomeu Melià (S. J.) (Journal de la Société des Américanistes)
The submission of the Guaraní language in the aftermath of Paraguayan independence. From the 17th century on, with a peak in the 18th century, vast amounts of literature written in Guaraní language were produced in the Jesuit-Guaraní settlements or Reductions of Paraguay. Some of the texts were published back then, but many remain in manuscript form in archives or libraries. This literature does not only deal with religious matters (catechisms, sermons, or devotional books). It also reflects the political, social and cultural life of the Guaraní people. In fact, these documents are not only written in Guaraní, but also written by Guaraní, and they continued to surface even after the Jesuits had been expelled from the settlements in 1768. Jesuitic Guaraní therefore seems to have outlived the Jesuits’ actual presence. By some strange paradox, after the proclamation of Paraguayan independence in 1811, Guaraní texts were no longer found, even though Paraguayans went on communicating in Guaraní language on a daily basis, as reported by numerous travellers who visited the country in the 19th century.